Pirates Past Noon : Magic Tree House #4 - Osborne, Mary Pope, 1949-; Murdocca, Sal (New York : Random House, 1994)
The magic treehouse whisks Jack and Annie back to the days of deserted islands, secret maps, hidden gold, and nasty pirates.
Too late! -- The bright blue sea -- Three men in a boat -- Vile booty -- The kid's treasure -- The whale's eye -- Gale's a-blowin' -- Dig, dogs, dig -- The mysterious M -- Treasure again.
"A First stepping stone book".
"RL: 2.2"--Cover p. [4].
"006-009"--Cover p. [4].
Accelerated Reader
Keywords: Pirates -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction